The Role of Artificial Intelligence (AI) in Transforming Physics Education: A Narrative Review - Verawati, Ni Nyoman Sri Putu; Nisrina, Nina (Lensa: Jurnal Kependidikan Fisika, 2024)
Artificial Intelligence (AI) has brought transformative changes to education, particularly in the field of physics, where complex concepts often pose significant challenges for students. This narrative review explores the role of AI in physics education by analyzing various tools and methods currently applied in learning environments, including intelligent tutoring systems, adaptive learning platforms, and interactive simulations. The study aims to assess the benefits and limitations of these technologies, as well as their potential to enhance learning outcomes through personalized, adaptive, and interactive experiences. Utilizing the SCOPUS database, a wide-ranging literature search was conducted with relevant keywords to capture studies that contribute to understanding AI’s impact on physics education. Results indicate that AI-driven tools significantly improve student engagement, accessibility, and understanding of abstract concepts by offering tailored learning pathways, real-time feedback, and immersive simulations. Additionally, AI provides alternative access to learning for students from diverse backgrounds, fostering inclusivity in physics education. However, challenges such as dependency on AI, ethical issues related to data security, and the potential digital divide are noted as barriers to effective implementation. To address these issues, the review recommends a balanced approach where AI complements traditional teaching methods, ensuring that it enhances rather than replaces human instruction. This review highlights the transformative potential of AI in physics education, advocating for further research to develop structured, ethical, and inclusive integration strategies that maximize the educational benefits of AI while addressing its limitations.